2011
DOI: 10.3109/s10165-010-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional disturbance of the stress-adaptation system in patients with scleroderma

Abstract: There have been several reports indicating the association between recent stress experiences and the onset or the exacerbation of rheumatic diseases, although few such reports exist in patients with scleroderma (SSc). The present study was performed to elucidate whether there were any functional disturbances in the neuro-endocrine-immune system as a homeostatic system upon stress in SSc patients. Various serum levels of stress-related hormones and cytokines were examined before and after a mental calculation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While we can only speculate on the putative mechanisms justifying this association, we are traced back to earlier reports of the co‐existence of phenylketonuria‐associated mental retardation and scleroderma [58]. Further, there are data suggesting that patients with SSc may have disturbances of the nervous system as represented by an impaired response to stress [59], the detection of central nervous system ischaemic vasculopathy at magnetic resonance imaging [60,61] and the changes in cerebrovascular reactivity [62].…”
Section: Discussionmentioning
confidence: 70%
“…While we can only speculate on the putative mechanisms justifying this association, we are traced back to earlier reports of the co‐existence of phenylketonuria‐associated mental retardation and scleroderma [58]. Further, there are data suggesting that patients with SSc may have disturbances of the nervous system as represented by an impaired response to stress [59], the detection of central nervous system ischaemic vasculopathy at magnetic resonance imaging [60,61] and the changes in cerebrovascular reactivity [62].…”
Section: Discussionmentioning
confidence: 70%
“…It has also been reported that the serum NE levels are significantly higher in SSc patients than in normal individuals 1 . In addition, the mental stress-induced serum NE levels are also higher in SSc patients than in normal individuals based on mental calculation stress tests, suggesting that SSc patients may have an impaired function of the neuro-endocrine-immune system due to stress 1 .…”
Section: Discussionmentioning
confidence: 98%
“…It has also been reported that the serum NE levels are significantly higher in SSc patients than in normal individuals 1 . In addition, the mental stress-induced serum NE levels are also higher in SSc patients than in normal individuals based on mental calculation stress tests, suggesting that SSc patients may have an impaired function of the neuro-endocrine-immune system due to stress 1 . Previous findings showed that serum NE levels in normal individuals were increased after cold exposure 2 , and serum NE levels increased after repeated cold-water immersions 3 , further indicate that emotional stress and cold exposure increase the systemic and/or local NE levels in SSc patients.…”
Section: Discussionmentioning
confidence: 98%